Effect of coconut, olive, and soybean oil on endotoxemia, inflammation, body composition, and metabolic status related to obesity - Cândido, Flávia Galvão (2016)
Objectives: To evaluate the effects of different fat types on lipopolysaccharides (LPS) translocation, systemic low-grade inflammation, body composition, and metabolic status in woman with excess body fat. Materials and methods. Original article 1: This is a randomized parallel arm study in which 78 excess body fat woman (aged 20 to 41y, mean ± standard error of 47.23 ± 0.48% of total body fat) were allocated to receive a drink containing 25mL of one of the three tested oils: coconut oil (CO, n = 23), extra-virgin olive oil (EVOO, n = 31), or soybean oil (SO, n = 24). Participants reported to the laboratory in a fasting state (12h). Blood samples were taken at baseline and 2 and 4h after starting one of the drinks. Triglycerides, LPS, and the citokines IL-8, IL-1β, IL-6, IL-10, TNF-α, and IL-12p70 concentrations were assessed. Original article 2: This is a randomized, double-blind, placebo-controlled clinical trial in which 41 excess body fat woman (aged 19 to 40y, 46.8 ± 0.6% of total body fat) consumed breakfasts containing 25mL of SO (control group, n = 20) or EVOO (n = 21) daily in the laboratory during nine consecutive weeks. Energy-restricted diets (-2090kJ, ~32%E) were prescribed. Anthropometric, body composition, blood pressure, and biochemical assessments were conducted in fasting state in the first and last day of experiment. Results. Original article 1: LPS concentrations were not affected by intervention. SO increased more triglicerydes and IL-8 than EVOO. CO was the only group that presented increase in IL-1β/IL-10 ratio. Changes in LPS were positively associated with pro-inflammatory profile only in CO. Original article 2: EVOO reduced diastolic blood pressure and increased total body fat loss in ~80% when compared to control group. There were a decrease in HDL-c and an increase in IL-10 in control group, while EVOO increased serum creatinine and reduced alkaline phosphatase (P between-groups > 0.050). Conclusions: The consumption of reasonable doses of distinct dietary fats influences postprandial systemic inflammation without changing plasma LPS concentrations. Detrimental changes were observed after consumption of SO and CO and correlation analyses suggested a synergic mechanism between CO and LPS-induced inflammation. Since EVOO contributed to improve fat loss and blood pressure, EVOO consumption should be stimulated in weight-loss programs.